MUSLIM CULTURAL IDENTITY AND ATTITUDE CHANGE AMONG TOLAKINESE COMUNITY IN KENDARI (JOURNAL OF INDONESIAN ISLAM, 2016)
This article analyses the changing attitude and cultural identity of Tolakinese Muslim Community in Kendari. It focuses on four cultural values: 1) kohanu (shy); 2) merou (courtesy); samaturu (solidarity); 4) taa ehe tunai tui (introspection). The findings shows that people in the rural area are generally maintaining their culture while people in urban area have a contrast attitude as cultural values have been degraded in practices. This degradation eventually resulted in the changing attitudes of Tolakinese society. In general, even though there is a small group of people who still understand and or practice the tradition, there is a trend of degradation in the cultural values. There are factors behind this trend, among them are: education, living in the city and mixed marriage. Realizing the potential extinction and the importance of the tradition, several efforts are taken by traditional leaders aiming at preserving the culture of Tolaki. Among the efforts are socialization and contextualization of the tradition in line with the development and the values of Islam.